Spinodal decomposition and the luminescence of Er in AlxIn1−xN:Er layers. Issue 1 (29th November 2012) - Yang, Miao; Weng, Ye; Strunk, Horst P.
Abstract Integrated photoluminescence intensities of the green lines from Er centers (2H11/2–4I15/2 and 4S3/2–4I15/2) embedded in AlxIn1−xN films are investigated in dependence of excitation energy and band gap energy of the film host. The films are deposited onto silicon and sapphire substrates by sputtering and subsequently annealed for optimization of the luminescence intensity. Two significant maxima of integrated intensity are observed. The first maximum appears, if the excitation energy matches the band gap energy of the AlxIn1−xN matrix. It can be explained by a bound exciton mediated energy transfer to Er centers. The second maximum occurs at below band gap energy excitation of some films with special compositions. These observations call for an adequate path for the excitation of Er. We propose a mechanism based on spinodal decomposition of AlxIn1−xN. In fact, our calculations and experiments (structure analysis in a transmission electron microscope) confirm that nanoparticles form of an In‐rich AlxIn1−xN phase, which can be assumed as quantum dots. Resonant energy transfer from these quantum dots into the luminescent centers can explain the Er luminescence enhancement.